Calbindin-D28k immunoreactivity in the pineal gland of the adult porcupine (Hystrix cristata) - Karan, Meryem; Timurkaan, Sema (Univ Zagreb Vet Faculty, 2012)
Distribution of the calbindin-D28k, an intracellular protein with a high affinity for calcium, was investigated immunohistochemically in the pineal gland of porcupine (Hystrix cristata). Two different types of cells were calbindin-D28k positive. The first was characterized by small sized cells. The second type of calbindin-D28k positive cells were characterized by their large size. Immunoreactive cells were found throughout the whole pineal gland without any preferential location, however they presented more densely around the base of the pineal stalk. Interstitial cells were calbindin-D28k negative.
Imunoreaktivnost mo?dane epifize odraslog dikobraza (Hystrix cristata) na kalbindin-D28k
Keywords: Calbindin-D28k; pineal gland; porcupine; immunohistochemistry